IDENTIFIKASI IKAN BERCAMPUR FORMALIN BERBASIS SENSOR GAS - Rouhillah; Ilham Hasbiullah; Ahmad Furgan (Politeknik Aceh, 2017)
The gas sensor used concept based on a contaminated air detection system can be used to detect dangerous objects. The main goal of this study is how to use a gas sensor to detect harmful gas such as formaldehyde. The problem found is the condition of the detected object must be dry to make the process faster. To find out the results of the detection, this research using interface result between microcontroller and personal computer that resulted change of ADC value by gas sensor array. On the whole tests, the change of ADC value reached 192 on TGS2600 sensor with formalized fish samples. Therefore, it can be concluded that the sensors can detect dangerous materials on an detected object in just 4 minutes with a flowrate of 0.8 atm/min (atmosphere per minutes).